2009
DOI: 10.1088/0957-4484/20/22/225303
|View full text |Cite
|
Sign up to set email alerts
|

Surface-enhanced Raman scattering on periodic metal nanotips with tunable sharpness

Abstract: This paper reports on a scalable bottom-up technology for producing periodic gold nanotips with tunable sharpness as surface-enhanced Raman scattering (SERS) substrates. Inverted silicon pyramidal pits, which are templated from non-close-packed colloidal crystals prepared by a spin-coating technology, are used as structural templates to replicate arrays of polymer nanopyramids with nanoscale sharp tips. The deposition of a thin layer of gold on the polymer nanopyramids leads to the formation of SERS-active sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 44 publications
2
60
0
Order By: Relevance
“…[2] The effectiveness of these sensors relies on two key aspects: the strong and selective binding of analyte to the sensor surface and the sensitivity of the optical response of the SP systems to changes in the local dielectric environment resulting from those binding events. As nanofabrication technologies have advanced, SP-based phenomena on nanostructured metal surfaces have been actively studied, [3][4][5][6][7][8][9][10] and the resolution limit has been constantly improved, to the point where sub-monolayer binding events can be detected. [11] A major limitation of these SP sensors is due to the lossy nature of their resonance modes, which results from strong absorption of light by the metal nanostructures themselves.…”
Section: Introductionmentioning
confidence: 99%
“…[2] The effectiveness of these sensors relies on two key aspects: the strong and selective binding of analyte to the sensor surface and the sensitivity of the optical response of the SP systems to changes in the local dielectric environment resulting from those binding events. As nanofabrication technologies have advanced, SP-based phenomena on nanostructured metal surfaces have been actively studied, [3][4][5][6][7][8][9][10] and the resolution limit has been constantly improved, to the point where sub-monolayer binding events can be detected. [11] A major limitation of these SP sensors is due to the lossy nature of their resonance modes, which results from strong absorption of light by the metal nanostructures themselves.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21] We have developed a scalable bottom-up technique for generating wafer-sized periodic gold nanopyramids with nanoscale tips as an efficient surface-enhanced Raman scattering substrate. [22][23][24] Here we demonstrate that the templated nanopyramids can also be utilized as sensitive SPR sensors for chemical and biological sensing. Finitedifference time-domain ͑FDTD͒ simulation has been conducted to complement the optical measurements.…”
mentioning
confidence: 77%
“…Linn's study showed that the arrays of nanotips structure could significantly enhance the local electromagnetic field and the sharpness of nanotips greatly affected the Raman enhancement. 13 Wu's report also demonstrated that in addition to the small gaps, the sharp tips of the conical structures showed strong Raman enhancement. 14 On the other hand, the angle resolved enhanced Raman scattering via different nanostructures was also studied in the literatures.…”
Section: Introductionmentioning
confidence: 94%
“…Such structures are capable of inducing very strong localized electric fields. 13,14,17 The localization of electric field is tighter for the tips structures due to the "hot spots" occupied at a smaller area compared to the blunter structures. Then, all tips of the protuberant Cu lines result in higher enhancement and the maximal enhancement factor reaches a plateau with an incident angle of 45…”
Section: -3 Huangmentioning
confidence: 99%